Robert B. Parker's buzz kill [large type] - Gaylin, Alison; Parker, Robert B., 1932-2010 (Parker, Robert B., 1932-2010. Sunny Randall novels, 2024)
"Sunny Randall is ready to lighten her load as a PI, until she is called upon by billionaire Bill Welch to investigate the disappearance of his son, Dylan, the cofounder of the Gonzo Energy Drink company. As Sunny traces the marks left behind by Dylan's past, she discovers not only his bad behavior with women, but also his reckless moves within the business world, producing an energy drink that has proven dangerous and even deadly. Who is Dylan, really? And why has he vanished? When bodies start to pile up, Sunny must find answers quick, before she gets caught in the crossfire"--